Type I IFN signaling in CD8– DCs impairs Th1-dependent malaria immunity - Varelias, Antiopi (2014)
Many pathogens, including viruses, bacteria, and protozoan parasites, suppress cellular immune responses through activation of type I IFN signaling. Recent evidence suggests that immune suppression and susceptibility to the malaria parasite, Plasmodium, is mediated by type I IFN; however, it is unclear how type I IFN suppresses immunity to blood-stage Plasmodium parasites. During experimental severe malaria, CD4+ Th cell responses are suppressed, and conventional DC (cDC) function is curtailed through unknown mechanisms. Here, we tested the hypothesis that type I IFN signaling directly impairs cDC function during Plasmodium infection in mice. Using cDC-specific IFNAR1-deficient mice, and mixed BM chimeras, we found that type I IFN signaling directly affects cDC function, limiting the ability of cDCs to prime IFN-γ–producing Th1 cells. Although type I IFN signaling modulated all subsets of splenic cDCs, CD8– cDCs were especially susceptible, exhibiting reduced phagocytic and Th1-promoting properties in response to type I IFNs. Additionally, rapid and systemic IFN-α production in response to Plasmodium infection required type I IFN signaling in cDCs themselves, revealing their contribution to a feed-forward cytokine-signaling loop. Together, these data suggest abrogation of type I IFN signaling in CD8– splenic cDCs as an approach for enhancing Th1 responses against Plasmodium and other type I IFN–inducing pathogens.